The Influence Of Career Development And Work Motivation On The Performance Of Employees Of The Regional Development Planning Agency Of South Lampung District - Febri, Wisnu; Sodirin, Sodirin (Utami Publisher, 2025)
The success of an agency in achieving its vision and mission needs to be supported by several indicators that will determine its success in achieving that vision and mission. One indicator in achieving the stated goals is the active role of employees or employees as one of the components of the organizational system. Employees have a major role in every organizational activity, because employees are planners, actors and determinants of the realization of organizational system goals. Organizational goals will be easier to achieve if employees have good work motivation. Employees who have high work motivation will be able to encourage these employees to work more enthusiastically and can make a positive contribution to the work they are responsible for. Work motivation is something that creates encouragement or enthusiasm for work or in other words, it drives work enthusiasm.The research objective in this thesis is to examine the influence of career development and work motivation on employee performance at the South Lampung Regional Development Planning Agency. This research uses a sampling research method with a total of 64 employees as respondents. Analysis was used using quantitative analysis and data processing using the SPSS program.The research results show that career development has a positive effect on employee performance with an influence contribution of 51.3%. Furthermore, work motivation also has a positive effect on employee performance with an influence contribution of 63.8%. The regression test shows that together there is a positive influence between career development and work motivation on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 68.3%, the remaining 31.7% is influenced by other variables outside this research.